2016
DOI: 10.1039/c5tc02927a
|View full text |Cite
|
Sign up to set email alerts
|

The impact of electrostatic interactions on ultrafast charge transfer at Ag29 nanoclusters–fullerene and CdTe quantum dots–fullerene interfaces

Abstract: We report how electrostatic interactions significantly impact charge transfer at CdTe QDs/fullerene interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…Simultaneously, a new broad absorption feature appears in the range of 500–560 nm, and an emission peak appears at approximately 507 nm. The intensities of these bands are enhanced with the increase in TCNE concentration, which suggests ground-state complex formation between the NCs and TCNE. …”
mentioning
confidence: 99%
“…Simultaneously, a new broad absorption feature appears in the range of 500–560 nm, and an emission peak appears at approximately 507 nm. The intensities of these bands are enhanced with the increase in TCNE concentration, which suggests ground-state complex formation between the NCs and TCNE. …”
mentioning
confidence: 99%
“…48 If only one type of quenching mechanism is taking place, the quenching can be expressed by the Stern − Volmer equation: [48][49][50][51][52][53][54][55][56] Dynamic quenching happens when the excited fluorophore comes in contact with the quencher molecule, which facilitates non-radiative transition to the ground state and the process leads to the quenching of fluorescence intensity.…”
Section: Fluorescence Response Of Alq 3 -Containing Block Copolymer Bmentioning
confidence: 99%
“…As shown in Fig.11, TNP solution shows two typical absorption bands at 365 nm and 251 nm. [51][52][53][54] Fig. Furthermore, the UV-vis absorption, excitation and emission spectra of the Alq 3 -containing block copolymer brush-GO hybrid were also measured in the absence and presence of TNP.…”
Section: Fig 12mentioning
confidence: 99%
“…Self-organization of [Au 102 ( p -MBA) 44 ] clusters into colloidal sheets and capsids were also driven by weak supramolecular forces . Moreover, noncovalent interactions were decisive in determining the assemblies formed by clusters with cyclodextrins (CDs) , and fullerenes. , Mathew et al showed that supramolecular functionalization of [Au 25 (SBB) 18 ] − (SBB is 4-( t -butyl)­benzyl mercaptan) clusters with CDs increased the stability of the cluster core and enhanced the luminescence of the cluster . Nag et al demonstrated that supramolecular complexation can lead to the emergence of interesting properties like isomerism in nanoclusters .…”
mentioning
confidence: 99%